1984
DOI: 10.1136/thx.39.11.809
|View full text |Cite
|
Sign up to set email alerts
|

Nedocromil sodium: a new drug for the management of bronchial asthma.

Abstract: ABSTRACr Nedocromil sodium (FPL 59002) is a pyranoquinoline dicarboxylic acid that has been developed for the management of bronchial asthma. We report the results of a double blind group comparative trial in which the disodium salt of nedocromil delivered by pressurised aerosol and a placebo were compared in the management of patients with a diagnosis of bronchial asthma who entered the double blind period on a minimum dose of beclomethasone dipropionate. In almost all the assessments of clinical activity ned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1985
1985
2000
2000

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…Nedocromil sodium protects against exercise induced asthma,' antigen induced bronchoconstriction,2 antigen induced nasal obstruction,3 and bronchoconstriction caused by nonspecific stimuli.4 When administered four times daily for one month, it improves the control of bronchial asthma. 5 The profile of action of nedocromil sodium is similar to that of sodium cromoglycate. Since sodium cromoglycate protects against bronchoconstrictor responses to sulphur dioxide6 we have investigated whether nedocromil sodium 2 or 4 mg confers similar protection against sulphur dioxide induced bronchoconstriction when compared with matched placebo.…”
mentioning
confidence: 93%
“…Nedocromil sodium protects against exercise induced asthma,' antigen induced bronchoconstriction,2 antigen induced nasal obstruction,3 and bronchoconstriction caused by nonspecific stimuli.4 When administered four times daily for one month, it improves the control of bronchial asthma. 5 The profile of action of nedocromil sodium is similar to that of sodium cromoglycate. Since sodium cromoglycate protects against bronchoconstrictor responses to sulphur dioxide6 we have investigated whether nedocromil sodium 2 or 4 mg confers similar protection against sulphur dioxide induced bronchoconstriction when compared with matched placebo.…”
mentioning
confidence: 93%
“…Nedocromil sodium is the disodium salt of a 1985; Shaw & Kay, 1985;Youngchaiyud & Lee, pyranoquinoline dicarboxylic acid which has been 1986) as well as being active in therapeutic trials developed as a new treatment (Tilade9, (Lal et al, 1984;Ruffin, 1986;Fairfax & Allbeson registered trade mark of Fisons plc) for reversible 1986). obstructive airways disease (Auty, 1986; A sensitive radioimmunoassay for nedocromil al., 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary studies in man have shown that nedocromil sodium reduces the symptoms of asthma and in addition it helps to relieve asthma in patients maintained on steroids (Lal et al, 1984). Further clinical work is needed to investigate the full potential ofthis new class ofdrug.…”
Section: 'Author For Correspondencementioning
confidence: 99%